Profesionalisme Apoteker dalam Perspektif Nilai Obat sebagai Amanah pada Teori Konstitusi Kesehatan Nusantara - Melsi Emilia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pharmacist professionalism is a key component in ensuring the quality of pharmaceutical services, encompassing not only compliance with technical and scientific standards but also a deep commitment to moral and ethical principles. In the Indonesian cultural context, the concept of